(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The present-day get rid of Soviet atheism, the issues of greatest interest is the recognition of spiritual life. Spirituality and even fashion, everything started to talk about religion. However, spirituality, faith, religion is a very subtle things, in order to provide them with the necessary knowledge to say is very dangerous. The article is currently registered in the country, one of the priests who served in the «Latter day saints, Jesus Christ, the Church» tells the congregation known as the Mormons. The authors noted that the theme of the lack of significant scientific work, mainly in the Russian scientific papers, Russian and Kazakh language Online article by the survey results. Due to be less than other data had to resort to the Internet. Key words: religion, new religious movements, mormons, «The Church of Jesus Christ of Latter-day Saints», Joseph Smith, Book of Mormon